Sco2 deficient mice develop increased adiposity and insulin resistance. (5th November 2017) - Hill, Shauna; Deepa, Sathyaseelan S.; Sataranatarajan, Kavithalakshmi; Premkumar, Pavithra; Pulliam, Daniel; Liu, Yuhong; Soto, Vanessa Y.; Fischer, Kathleen E.; Van Remmen, Holly
Abstract: Cytochrome c oxidase (COX) is an essential transmembrane protein complex (Complex IV) in the mitochondrial respiratory electron chain. Mutations in genes responsible for the assembly of COX are associated with Leigh syndrome, cardiomyopathy, spinal muscular atrophy and other fatal metabolic disorders in humans. Previous studies have shown that mice lacking the COX assembly protein Surf1 ( Surf1 −/− mice) paradoxically show a number of beneficial metabolic phenotypes including increased insulin sensitivity, upregulation of mitochondrial biogenesis, induction of stress response pathways and increased lifespan. To determine whether these effects are specific to the Surf1 mutation or a more general effect of reduced COX activity, we asked whether a different mutation causing reduced COX activity would have similar molecular and physiologic changes. Sco2 knock-in/knock-out (KI/KO) mice in which one allele of the Sco2 gene that encodes a copper chaperone required for COX activity is deleted and the second allele is mutated, have previously been shown to be viable despite a 30–60% reduction in COX activity. In contrast to the Surf1 −/− mice, we show that Sco2 KI/KO mice have increased fat mass, associated with reduced β-oxidation and increased adipogenesis markers, reduced insulin receptor beta (IR-β levels in adipose tissue, reduced muscle glucose transporter 4 (Glut4) levels and a impaired response to the insulin tolerance test consistent with insulin resistance. COX activity and protein are reduced approximately 50% in adipose tissue from the Sco2 KI/KO mice. Consistent with the increase in adipose tissue mass, the Sco2 KI/KO mice also show increased hepatosteatosis, elevated serum and liver triglyceride and increased serum cholesterol levels compared to wild-type controls. In contrast to the Surf1 −/− mice, which show increased mitochondrial number, upregulation of the mitochondrial unfolded protein response (UPR MT ) pathway and no significant change in mitochondrial respiration in several tissues, Sco2 KI/KO mice do not upregulate the UPR MT, and tissue oxygen consumption and levels of several proteins involved in mitochondrial function are reduced in adipose tissue compared to wild type mice. Thus, the metabolic effects of the Sco2 and Surf1 −/− mutations are opposite, despite comparable changes in COX activity, illuminating the complex impact of mitochondrial dysfunction on physiology and pointing to an important role for complex IV in regulating metabolism.